Literatur in Österreich 1938-1945. Salzburg - Gradwohl-Schlacher, Karin (2021)
The present book about Salzburg is volume 6 of an encyclopedic reference work that, as a result of basic research in literary studies, represents the first systematic attempt towards a comprehensive documentation of the literary life of Austria during the Nazi era. From its methodological approach, it is intended to make the literary events that took place within the official system of the Third Reich as promoted, or at least tolerated, by the decicionmakers in the cultural industry more accessible, without resorting to limiting, biased attemps to define a canon.